The Preeclampsia Free Village Initiative Through Early Detection Among Pregnant Women in the Service Area of the Kokop Community Health Care - Ermawati, Zaitun; Anggraeni, Novi; M. Hasinuddin; Susanti, Eny (Universitas Muhammadiyah Sidoarjo, 2026)
WHO (World Health Organization) estimates that pre- The The exact causes of preeclampsia and eclampsia remain unclear. Several studies have examined factors influencing preeclampsia occurrence. Radjamuda and Montolalu identified age and history of hypertension (preeclampsia) as associated factors This study aimed to analyze differences in the number of high-risk preeclampsia cases detected before and after implementation of the preeclampsia-free village movement method. The study employed a quasi-experimental design using a one-group pretest–posttest approach. Research subjects were selected through simple random sampling, with a total sample of 38 participants. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. The statistical analysis yielded a significance value of 0.000, whichis lower than α = 0.05, indicating a statistically significant increase and a significant difference in the number of high-risk preeclampsia cases detected before and after the implementation of the preeclampsia-free village movement method.